Tuning the Solubility of Soluble Support Constructs in Liquid Phase Oligonucleotide Synthesis - Rosenqvist, Petja; Saari, Verneri; Ora, Mikko; Molina, Alejandro Gimenez; Horvath, Andras; Virta, Pasi (AMER CHEMICAL SOC, 2026)
Solubility of the growing oligonucleotide-soluble support constructs in the liquid phase oligonucleotide synthesis (LPOS) is a critical parameter, which affects coupling efficiency, purity, and recovery of the growing oligonucleotides during the chain elongation. In the present study, oligonucleotides have been assembled on a 4-oxoheptanedioic acid (OHDA) linker-derived tetrapodal soluble support using 5 '-O-(2-methoxyprop-2-yl)-protected 2 '-deoxyribonucleotide phosphoroamidite building blocks with different nucleobase protecting groups [isobutyryl (Gua), 1-butylpyrrolidin-2-ylidene (Gua, Cyt), 2,4-dimethylbenzoyl (Ade, Cyt), and Bz (Thy)]. The solubility of the oligonucleotide-soluble support constructs (molecular mass varying between 3 and 10 kDa) as models of protected tetra-, octa-, dodeca-, hexadeca-, and eicosa-nucleotides was measured in different solvent systems and in potential antisolvents. By tuning the nucleobase protecting group scheme, the solubility can be improved in aprotic organic solvent systems, while the recovery of the constructs in the precipitation, used for the isolation and purification of the growing oligonucleotide intermediates in a protic antisolvent (2-propanol), remained near quantitative. The precipitation-based yield of the protected tetrapodal oligonucleotides varied from a quantitative to 90% yield. Overall yield (for di-: 95%, tri-: 79-96%, tetra-: 82-88%, and pentanucleotides: 68-75%) and purity of the LPOS were evaluated by RP HPLC and MS-spectroscopy of the released oligonucleotide aliquots. In addition, the orthogonality of the OHDA linker was applied to release authentic protected nucleotides from the soluble supports.